Analysis of FWB (Friends With Benefits) Behaviour Phenomenon among Adolescents through Social Media in the Information Technology Era (Departement of Comparative Study of Religions, 2023)
In the current era of information technology development, both the positive and negative impacts of technology have garnered significant attention from society. One of the issues emerging in the realm of information technology is the phenomenon of friendship with sexual benefits, commonly known as “Friends with Benefits” (FWB). This issue presents substantial implications for adolescents. The purpose of this research is to analyze the FWB behavior phenomenon among adolescents through the observation of social media. The study employs a qualitative descriptive approach. Primary data sources comprise books, journals, and written materials relevant to the FWB phenomenon and adolescent behavior. Secondary data is obtained from observations of social media and relevant websites. Data analysis involves the collection, filtering, and interpretation of content related to FWB behavior and its impact on adolescents. The research findings indicate that FWB behavior among adolescents today significantly influences moral deviations and social norms. While interactions between males and females within the FWB context inherently involve dimensions of sexuality, many adolescents perceive it merely as entertainment. This phenomenon underscores a gap between sexual gratification devoid of emotional attachment and commitment-based relationships. Consequently, FWB behavior has the potential to undermine societal and religious norms that govern interpersonal relationships